Differences in Vital Signs of Chronic Kidney Failure Patients Before and After Hemodialysis at The Mount Djati Cirebon Regional Hospital - Trihandayani, Yani; Marwati; Ruswati; Supriatin, Titin (Jurnal Penelitian Pendidikan IPA, 2024)
Disease No contagious, especially Fail Kidney Chronic (GGK), is problem significant health impacts in Indonesia, with prevalence increase from 2.0 to 3.8% in 2018. Hemodialysis is therapy main used​ for handling GGK, which is done on average two to three times per week. Research This aiming for identify difference Vital signs of GGK patients before and after hemodialysis at Gunung Jati Regional Hospital, Cirebon. Research This use cross-sectional design with one group pre-test and post-test approach. Research results show change significant on pressure blood, frequency pulse, breathing, temperature body, and saturation oxygen after hemodialysis. There were 59% of patients experience pressure blood tall before hemodialysis, and 61% of patients experience temperature body low after hemodialysis. Research This emphasize importance monitoring hemodynamics in CKD patients for prevent more complications​ critical during and after procedure hemodialysis